Diversity of lithophytic moss species in karst regions in response to elevation gradients. - Yalin Jin; Xiurong Wang (PLoS ONE, 2023)
The distribution pattern of species diversity along various elevation gradients reflects the biological and ecological characteristics of species, distribution status and adaptability to the environment. Altitude, a comprehensive ecological factor, affects the spatial distribution of species diversity in plant communities by causing integrated changes in light, temperature, water and soil factors. In Guiyang City, we studied the species diversity of lithophytic mosses and the relationships between species and environmental factors. The results showed that: (1) There were 52 species of bryophytes in 26 genera and 13 families within the study area. The dominant families were Brachytheciaceae, Hypnaceae and Thuidiaceae. The dominant genera were Brachythecium, Hypnum, Eurhynchium, Thuidium, Anomodon and Plagiomnium; The dominant species were Eurohypnum leptothallum, Brachythecium salebrosum, Brachythecium pendulum etc. The number of family species and dominant family genera increased first and then decreased with the increase of altitude, and their distribution in elevation gradient III (1334-1515m) was the largest, with 8 families, 13 genera and 21 species. The elevation gradient I (970-1151m) was the least species distributed, with 5 families, 10 genera and 14 species. The dominant species with the largest number in each elevational gradient were Eurohypnum leptothallum, Brachythecium pendulum, Brachythecium salebrosum and Entodon prorepens; (2) There were five kinds of life forms in different elevation gradients, including Wefts, Turfs, Mat, Pendants and Tail. Among them, wefts and turfs appeared in all elevations, while a small amount of Pendants appeared in the area of elevational gradient I (970-1151m), and the most abundant life form was found in the range of elevational gradient III (1334-1515m); (3) Patrick richness index and Shannon-Wiener diversity index were highly significantly (p<0.01) positively correlated, both of which increased and then decreased with elevation, reaching a maximum at elevation gradient III (1334-1515m); The Simpson dominance index had a highly significant (p<0.01) negative correlation with the Patrick richness index and the Shannon-Wiener diversity index, which showed a decreasing and then increasing trend with increasing altitude; Pielou evenness index showed no discernible trend; (4) β diversity study revealed that while the similarity coefficient tended to decrease with increasing altitude, the species composition of bryophytes increased. The elevation gradient II (1151-1332m) and elevation gradient I (970-1151m) shared the most similarities, whereas elevation gradient III (1515-1694m) and elevation gradient I shared the least similarities (970-1151m). The findings can enrich the theory of the distribution pattern of lithophytic moss species diversity at distinct elevation gradients in karst regions, and serve a scientific and reasonable reference for restoring rocky desertification and protecting biodiversity there.